Modeling of ozone precursors and their transformation into ground-level ozone in urban environment in Malaysia - Ghazali, Nurul Adyani (2010)
Ozone (O3) is one of the major problems of air pollution around the world due to its ability to cause adverse effect to human health and environment. Hence, it is important to develop O3 prediction model to give the early warning to public. The hourly observations of O3 and nitrogen oxides (NOx) concentrations together with the weather parameters were monitored from five study areas in Malaysia. The observations were obtained over five year period from 2003 to 2007. Times series plot was used to explain the transformation of nitrogen dioxide (NO2) into O3 at urban environment of Malaysia. The findings proved that the peak concentration of O3 occurs during noon when highest UVB intensity and temperature recorded. By using multiple linear regression analysis, O3 prediction daytime and night time models for each study areas were developed based on its precursors;